The Effect Of Fins Training On Leg Strength Of Freestyle Swimming In Beginner Swimmer At Garuda Laut Palopo - Asrianti Asrianti; Rasyidah Jalil; Imam Pribadi (STKIP Muhammadiyah Kuningan, 2023)
The research is based on the increasing interest in swimming in the community and trying to provide an understanding that there are methods that can be used to increase the swimmers’ leg strength, especially freestyle swimming, by training methods using fins tools. Fins are one of the tools commonly used in diving. Fins consist of various types, including kaki kayak. Kaki kayaks or fins are made of rubber with widened shapes at the ends of the feet. Fins are swimming tools with many benefits, such as increasing propulsion speed for swimming practice. By using fins, swimmers can train leg muscle strength and produce swimming speed rates on freestyle legs; these fins can optimally increase the power of the legs and flex freestyle leg swings. Fins can also train flexibility in the ankles. The research used is quantitative research using experimental methods and the Discovery Learning approach. Discovery Learning is a method that aims to guide students to gain concepts from various data found through observation and experimentation. The research design used in this study is a one-group pretest-posttest design to compare conditions before and after treatment. Subjects from This research is a beginner swimmer at Garuda Laut Palopo, and this practice is carried out in the Wae Kambass swimming pool. The sample in this study were novice swimmers at the Palopo Sea Garuda. The population of this study is all beginner swimmers who are members of the Palopo Laut Garuda Club, totaling 15 people. Samples were taken by setting the age criteria of 9-21 years; novice swimmers included in this criterion counted ten people. The results of the research and discussion of the data obtained using a statistical approach concluded that there was a